Carrier frequency of F508del mutation of cystic fibrosis in medical students from Universidad del Rosario, Bogotá, Colombia (2007)
Introduction: Cystic fibrosis (CF) is the most frequent autosomical recessive disorder in Caucasian population with an incidence of in 2000 newborns. The disease is caused by mutations in the cfr gene, but the most common mutation is F508del, which accounts for 66% of CF chromosomes worldwide and a carrier frequency for Caucasian population of 1 in 25. Objective: To determine the carrier frequency of the F508del mutation in 110 unrelated, healthy students from the Facultad de Medicina, Universidad del Rosario. Methods. The presence of F508del mutation using PCR and heteroduplex analysis was determined. Results: Only four heterozygotes for F508del mutation were discovered. This represents a carrier frequency of 1 in 27 students. Conclusions: This estimated frequency of F508del carriers is higher than expected, encouraging further'screening in normal control individuals from different regions of Colombia. © 2007 Corporación Editora Médica del Valle.